Patterns of obesity-related health behaviors and parental monitoring in children - Moss, Haley, author; Thomson, Elizabeth, author; Butki, Brian, author; Li, Kaigang, author (Colorado State University. Libraries, 2017)
In America, one in five children are overweight or obese by five years of age. By the time obese children reach adulthood, obesity suppressing and promoting habits could be set and hard to change. We looked to see what age these habits begin to form using a survey-based study of children enrolled in the Youth Sports Camps run by the Department of Health and Exercise Science at CSU. Determining the age of habit development will allow us to create effective interventions targeting this critical period that deter or prevent the onset of obesity.
199 - Haley Elizabeth Moss
Dynamic profiles of health habits in children: what, where, when intra-programs
Keywords: obesity; prevention; habits